Analysis of Mll1 Deficiency Identifies Neurogenic Transcriptional Modules and Brn4 as a Factor for Direct Astrocyte-to-Neuron Reprogramming. Issue 4 (30th May 2014) - Potts, Matthew B.; Siu, Jason J.; Price, James D.; Salinas, Ryan D.; Cho, Mathew J.; Ramos, Alexander D.; Hahn, Junghyun; Margeta, Marta; Oldham, Michael C.; Lim, Daniel A.
Abstract: BACKGROUND: Mixed lineage leukemia-1 ( Mll1 ) epigenetically regulates gene expression patterns that specify cellular identity in both embryonic development and adult stem cell populations. In the adult mouse brain, multipotent neural stem cells (NSCs) in the subventricular zone generate new neurons throughout life, and Mll1 is required for this postnatal neurogenesis but not for glial cell differentiation. Analysis of Mll1 -dependent transcription may identify neurogenic genes useful for the direct reprogramming of astrocytes into neurons. OBJECTIVE: To identify Mll1 -dependent transcriptional modules and to determine whether genes in the neurogenic modules can be used to directly reprogram astrocytes into neurons. METHODS: We performed gene coexpression module analysis on microarray data from differentiating wild-type and Mll1 -deleted subventricular zone NSCs. Key developmental regulators belonging to the neurogenic modules were overexpressed in Mll1 -deleted cells and cultured cortical astrocytes, and cell phenotypes were analyzed by immunocytochemistry and electrophysiology. RESULTS: Transcriptional modules that correspond to neurogenesis were identified in wild-type NSCs. Modules related to astrocytes and oligodendrocytes were enriched in Mll1 -deleted NSCs, consistent with their gliogenic potential. Overexpression of genes selected from the neurogenic modules enhanced the production of neurons from Mll1 -deleted cells, and overexpression of Brn4 (Pou3f4) in nonneurogenic cortical astroglia induced their transdifferentiation into electrophysiologically active neurons. CONCLUSION: Our results demonstrate that Mll1 is required for the expression of neurogenic but not gliogenic transcriptional modules in a multipotent NSC population and further indicate that specific Mll1 -dependent genes may be useful for direct reprogramming strategies.